Association of thirty-year alcohol consumption typologies and fatty liver: Findings from a large population cohort study. (1st January 2019) - Britton, Annie; Mehta, Gautam; O'Neill, Dara; Bell, Steven
Highlights: We report the association between 30-year drinking typologies and risk of fatty liver disease. People with sustained heavy drinking during midlife had greater risk of fatty liver than stable moderate drinkers at early old age. We also observed that sustained moderate drinkers did not have reduced risk of fatty liver compared to stable non-drinkers. These findings indicate that the drinking habits adopted by adults during midlife affect the development of fatty liver disease and cast doubt on the protective benefit of light-drinking. Abstract: Objective: To evaluate the longitudinal relationship between repeated measures of alcohol consumption and risk of developing fatty liver. Patients and methods: This study includes 5407 men and women from a British population-based cohort, the Whitehall II study of civil servants, who self-reported alcohol consumption by questionnaire over approximately 30 years (1985–1989 through to 2012–2013). Drinking typologies during midlife were linked to measures of fatty liver (the fatty liver index, FLI) when participants were in older age (age range 60–84 years) and adjusted for age, socio-economic position, ethnicity, and smoking. Results: Those who consistently drank heavily had two-fold higher odds of increased FLI compared to stable low-risk moderate drinkers after adjustment for covariates (men: OR = 2.04, 95%CI = 1.53–2.74; women: OR = 2.24, 95%CI = 1.08–4.55). Former drinkers also had an increased FLI compared to low-risk drinkers (men: OR = 2.09, 95%CI = 1.55–2.85; women: OR = 1.68, 95%CI = 1.08–2.67). There were non-significant differences in FLI between non-drinkers and stable low-risk drinkers. Among women, there was no increased risk for current heavy drinkers in cross sectional analyses. Conclusion: Drinking habits among adults during midlife affect the development of fatty liver, and sustained heavy drinking is associated with an increased FLI compared to stable low-risk drinkers. After the exclusion of former drinkers, there was no difference between non-drinkers and low-risk drinkers, which does not support a protective effect on fatty liver from low-risk drinking. Cross-sectional analyses among women did not find an increased risk of heavy drinking compared to low-risk drinkers, thus highlighting the need to take a longitudinal approach.